Electronic structure and composition of tin oxide thin epitaxial and magnetron layers according to synchrotron XANES studies - Olga A. Chuvenkova; Nikolai I. Boikov; Stanislav V. Ryabtsev; Elena V. Parinova; Ratibor G. Chumakov; Alexei M. Lebedev; Dmitry Smirnov; Anna Makarova; Sofiia S. Titova; Kirill A. Fateev; Sergey Yu. Turishchev (Конденсированные среды и межфазные границы, 2024)
The materials of the tin-oxygen system and thin-film structures based on them are modern and actual for the creation of a wide range of electronic devices, for example, resistive gas sensors of high sensitivity and short response time with low energy consumption and high manufacturability. An important direction in the study of such materials and structures is the control of properties with variations in technological formation regimes. Information on the composition, local atomic and electronic structure of thin layers of the tin-oxygen system with varying approaches to their production is in demand.